VASORELAXANT MECHANISM(S) OF CLERODENDRUM VOLUBILE ETHANOL LEAF EXTRACT IN NORMAL AND DOXORUBICIN-TREATED ENDOTHELIUM INTACT AORTIC RINGS - AKINSOLA, AKINYELE OLUBIYI; ADENEYE, ADEJUWON ADEWALE; OLORUNDARE, OLUFUNKE ESAN; SALAHDEEN, HUSSEIN MOYOSORE; MURTALA, BABATUNDE ADEKUNLE; MUKHTAR, HASSAN; ALBRECHT, RALPH M. (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Doxorubicin (DOX) is a highly effective antibiotics anthracycline cytotoxic agent with a broad spectrum of activity in the treatment of solid and hematological malignancies. However, DOX is notorious for inducing cardiotoxicity and vascular dysfunction as its common off-target side effects. This study evaluated the possible vasorelaxant activity and mechanism(s) of action of Clerodendrum volubile ethanol leaf extract (CVE) in normal and DOX-pretreated endothelium intact aortic rings in Physiological Salt Solution (PSS) in vitro. Methods: The responses were recorded isometrically by an organ bath connected to Data Capsule Acquisition System. Effects of CVE on phenylephrine-precontracted endothelium intact rat aortic rings and the influence of the respective blockers for adrenergic, cholinergic, calcium channel, and prostacyclin receptors were investigated to unveil the possible underlying vasorelaxant mechanism(s) of CVE. Results: Our findings showed that CVE significantly induced vasorelaxation in phenylephrine hydrochloride (PE) and KCl precontracted endothelium intact aortic rings in a concentration-dependent manner. Furthermore, the CVE-induced vasorelaxation in PE- and KCl-precontracted aortic rings were inhibited by pre-incubation with atropine and indomethacin indicating that the vasorelaxant effect of CVE was profoundly mediated through cholinergic and prostacyclin mechanisms. Conclusion: Overall, results of this study report for the first time the vasorelaxant effect of CVE in isolated endothelium-intact doxorubicin-treated aortic rings of normotensive rats which was probably cholinergic and prostacyclin-mediated. Thus, results of this study provide further insight into the cardioprotective mechanism of CVE in doxorubicin-induced cardiotoxicity beyond the antioxidant and anti-apoptosis mechanisms that have been previously reported.